The Creation of a Mobile Educational Outreach Unit for Visual Arts Exhibitions - Rojanatanti, Monvilai (Journal of Urban Culture Research, 2014)
The art scene in Thailand is evidently active and vibrant with numerous art spaces and galleries established in many regions of the country. However this is only one side of the art movement in Thailand. On the other side, who is the audience for this growth? This research aims to tighten the gap between visual arts exhibitions and their audience as well as arguing for the importance of educational programs that should be attached to the visual arts exhibitions in the art institutions of Thailand. The research also aims to search for the medium that shows how visual arts exhibitions can educate and cultivate audiences as well as shape their hearts and souls leading to good citizenship. The Mobile Educational Outreach Unit is comprised of a database of materials to be presented to both existing and potential audiences of art institutions. The Mobile Educational Outreach Unit can help increase the size of the audience visiting art institutions by enhancing their understanding of art, which is one of the main missions of these institutions. Moreover, all the data collected in the Mobile Unit will be a beneficial addition to the visual art archives of Thailand.